Structural Mechanisms of Quasi-2D Perovskites for Next-Generation Photovoltaics - Hyeonseok Lee; Taeho Moon; Younghyun Lee; Jinhyun Kim (Nano-Micro Letters, 2025)
Highlights This review highlights the structural advantages and challenges of qausi-2D perovskite. Beyond these structural adaptations, unique additive methods specific to quasi-2D perovskites are suggested, alongside future directions for further improvement. Material and device analysis using Ruddlesden–Popper, Dion–Jacobson, and alternating cation phases are discussed.